The effect of the pulse repetition rate on the fast ionization wave discharge. (10th May 2018) - Huang, Bang-Dou; Carbone, Emile; Takashima, Keisuke; Zhu, Xi-Ming; Czarnetzki, Uwe; Pu, Yi-Kang
Abstract: The effect of the pulse repetition rate (PRR) on the generation of high energy electrons in a fast ionization wave (FIW) discharge is investigated by both experiment and modelling. The FIW discharge is driven by nanosecond high voltage pulses and is generated in helium with a pressure of 30 mbar. The axial electric field ( E z ), as the driven force of high energy electron generation, is strongly influenced by PRR. Both the measurement and the model show that, during the breakdown, the peak value of E z decreases with the PRR, while after the breakdown, the value of E z increases with the PRR. The electron energy distribution function ( EEDF ) is calculated with a model similar to Boeuf and Pitchford (1995 Phys. Rev . E 51 1376). It is found that, with a low value of PRR, the EEDF during the breakdown is strongly non-Maxwellian with an elevated high energy tail, while the EEDF after the breakdown is also non-Maxwellian but with a much depleted population of high energy electrons. However, with a high value of PRR, the EEDF is Maxwellian-like without much temporal variation both during and after the breakdown. With the calculated EEDF, the temporal evolution of the population of helium excited species given by the model is in good agreement with the measured optical emission, which also depends critically on the shape of the EEDF .